An augmented state observer-based sensorless control of grid-connected inverters under grid faults. (December 2021) - Benyamina, Fayçal; Benrabah, Abdeldjabar; Khoucha, Farid; Zia, Muhammad Fahad; Achour, Yahia; Benbouzid, Mohamed
Highlights: System modeling in PNS under synchronous reference frame. Augmented state and disturbance observer for voltage and angular frequency estimation. GCs requirement-based LVRT strategy used to enhance grid stability. Double frequency active power oscillations suppression. Abstract: The increasing integration of grid-connected renewable energy systems impose major challenges of reliability and power quality within power grid system. Grid-connected systems must ensure grid stability, accommodate low voltage ride-through capability, and comply with grid codes under unbalanced voltage dips to avoid any grid-disconnection. In this context, this paper proposes a novel control strategy to improve grid-connected inverter control under unbalanced grid voltage conditions. Positive and negative sequence components of grid voltage are estimated using an augmented state and disturbance observer. The estimated values of grid voltage and phase-angle are used to protect the inverter from any over-current tripping even at unbalanced grid voltage dips. This can be achieved by reducing active power and suppressing its fluctuations with new current references, which are obtained in the synchronous reference frame according to grid codes. The effectiveness and flexibility of the proposed power control strategy have been demonstrated by numerical simulation and validated by experiments in both balanced and unbalanced grid fault conditions.